Larklight eaudiobook A rousing tale of dauntless pluck in the farthest reaches of space. - Reeve, Philip (Larklight, 2007)
Author Philip Reeve was shortlisted for the Whitbread Prize Children's Book Award. In 1851 a mysterious visitor to Art Mumby's space home has plans for a calamity that will destroy not only the entire British Empire, but also the known universe. Can disaster be prevented with help from Art's irritating sister Myrtle, a few exotic space creatures, and an extraterrestrial pirate? "Both the story line and the language demonstrate Reeve's respect for his readership."-Booklist